Clinico-Haematological Profile of Acute Megakaryoblastic Leukaemia: Report of Five Cases - Sunita Sharma; Anita Nangia; Sonal Jain Malhotra; Shashi Narayan; Aparna Harbhajanka; Sarika Singh (Advances in Hematology)
Acute megakaryoblastic leukemia (AMKL) is a rare subtype of acute myeloid leukemia. Although known as a distinct entity for a very long time, because of lack of distinct clinical features and morphological criteria, it is difficult to diagnose this variant correctly. We herein present the clinical, morphological, cytochemical, and immunocytochemical features of five cases of AMKL. Certain morphological features such as presence of abnormal platelet count, giant platelets, and cytoplasmic blebbing in blasts were found to be important pointers towards the diagnosis. However, none of the features were found to be consistent and thus morphological diagnosis has to be confirmed by cytochemistry and immunocytochemistry.